2011
DOI: 10.1016/s1413-8670(11)70159-3
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial and community infections due to class A extended-spectrum β-lactamase (ESBLA)-producing Escherichia coli and Klebsiella spp. in southern Brazil

Abstract: ESBL-producing E. coli, and especially K. pneumoniae are essentially a nosocomial problem, and their dissemination to the community is relatively limited. The great genetic variability observed among ESBL-producing bacteria indicates polyclonal spread and high transference of ESBL genes between bacteria in the hospital environment. This information is of paramount importance for nosocomial infection control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
1
14
1
2
Order By: Relevance
“…The high genetic variability observed among ESBLproducing bacteria indicates polyclonal spread to K. pneumoniae, E. cloacae, and E. coli and a high rate of transfer of ESBL genes between bacteria in healthcare-associated infections. Other Brazilian studies have found similar results (13) (30) . Polyclonal dissemination is also supported by the incidence of identical clones with different types of CTX-M ESBLs as well as by unrelated isolates expressing identical enzymes.…”
Section: Analysis Of Genetic Similaritysupporting
confidence: 75%
See 2 more Smart Citations
“…The high genetic variability observed among ESBLproducing bacteria indicates polyclonal spread to K. pneumoniae, E. cloacae, and E. coli and a high rate of transfer of ESBL genes between bacteria in healthcare-associated infections. Other Brazilian studies have found similar results (13) (30) . Polyclonal dissemination is also supported by the incidence of identical clones with different types of CTX-M ESBLs as well as by unrelated isolates expressing identical enzymes.…”
Section: Analysis Of Genetic Similaritysupporting
confidence: 75%
“…The carbapenems are the most widely used antimicrobial agents to treat infections caused by ESBL-producing strains (9) (10) . However, the indications for their use should be clearly defi ned because the indiscriminate use of carbapenems has led to the emergence of resistant strains (30) . The clinical isolates analyzed in our study were susceptible to tigecycline but to a lesser degree than they were to carbapenems.…”
Section: Analysis Of Genetic Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Some Pantoea species cause infections in humans (Del etoile et al, 2009). The pathogenicity of K. michiganensis, isolated from a toothbrush holder (Saha et al, 2013), has not been reported yet, although its presence may be considered undesirable in ice due to its ability to form biofilms (Saha et al, 2014) and since the Klebsiella genus includes clinically relevant species (Wollheim et al, 2011).…”
Section: Figmentioning
confidence: 99%
“…Wollheim et al, 2011) Celenza et al, 2006. detectaram em seu estudo na Bolívia, genes bla CTX-M em 92% das enterobactérias estudadas, um percentual igual aos valores do presente estudo.…”
unclassified